Pengaruh Total Asset Turnover dan Pertumbuhan Penjualan Terhadap Return on Equity pada PT Indo Acidatama, Tbk - Alhumaira, Adinda Faudila; Alwi; Mukhlis (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The purpose of this research is to determine the effect of Total Asset Turnover and Sales Growth on Return on Equity at PT. Indo Acidatama, Tbk. This type of research is associative using a research instrument in the form of a list of tables. The research population is all annual financial reports of PT. Indo Acidatama, Tbk for the period 2008 to 2022. The sample for this research is 11 annual reports (total assets, total capital, sales and net profit) of PT. Indo Acidatama, Tbk for the period 2012 to 2022 using the purposive sampling method. The data collection techniques for this research are documentation and literature study. The data analysis technique uses classical assumption tests (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test), followed by multiple linear regression analysis, multiple correlation coefficient, t test and f test. The research results show that total asset turnover and sales growth have a significant simultaneous influence on return on equity at PT. Indo Acidatama,